Properties of novel biodegradable film from gelatin capsule waste as influenced by various solvents and washing cycles - Pudthaya Kumnerdsiri; Sasina Sanprasert; Anusorn Seubsai; Jaksuma Pongsetkul; Nathdanai Harnkarnsujarit; Saroat Rawdkuen; Samart Sai-ut; Suphat Phongthai; Piyangkun Lueangjaroenkit; Ekasit Onsaard; Ali Muhammed Moula Ali; Thomas Karbowiak; et al. (Future Foods)
Biodegradable films, featuring eco-friendly attributes, offer a promising solution to environmental pollution and ecological challenges, serving as a viable alternative to synthetic polymer packaging films. This study investigates the washing process with various solvents (ethanol and water) and washing cycles (1 and 3 times) on the properties of gelatin capsule waste films (GCWF). The washing process could improve properties such as tensile strength, thermal properties, transparency value, and solubility by eliminating oil droplets from the raw materials. The GCWF washed by ethanol (GCWF Alc) exhibited higher tensile strength (TS), thermal properties, and transparency value compared with GCWF washed by water (GCWF W). Increasing the number of washing cycles could also enhance the efficiency of eliminating oil droplets from the raw materials. The complete degradation of GCWF in soil was observed on day 15 after burial. FTIR spectroscopy revealed differences in bands and patterns between control film (GCWF) and washed films (GCWF Alc and GCWF W). These findings highlight the potential of the washing process in enhancing film properties, and the utilization of gelatin capsule waste as biodegradable films could be further developed for food packaging applications, contributing to environmentally friendly technologies